Hypoglycemic effect of the dry leaf extract of Myrcia multiflora in streptozotocin-induced diabetic mice. (10th May 2023) - Oliveira, Edinilze S.C.; Acho, Leonard D.R.; Morales-Gamba, Ruben Dario; do Rosário, Alessandro S.; Barcellos, José Fernando M.; Lima, Emerson S.; Machado, Marcos B.
Abstract: Ethnopharmacological relevance: Myrcia multiflora (Lam) DC . is a medicinal plant used in folk medicine for diabetes control, mainly in the Brazilian Amazon. The leaves of this species has already demonstrated antidiabetic properties; however, in mice with type 2 diabetes (DM2), the cumulative effect of the consumption of the dry extract of M. multiflora leaves (Mm) has not yet been reported. Aim of the study: To investigate the effect of the dry extract obtained from the infusion of the dried leaves of M. multiflora on the blood glucose levels of diabetic mice. Materials and methods: DM2 was induced in Swiss male mice by a single intraperitoneal injection of streptozotocin [150 mg/kg body weight (bw)]. The animals were divided into two control groups (healthy and diabetic without treatment) and three sample groups that received Mm (25 and 50 mg/kg bw) and acarbose (200 mg/kg bw) by gavage once daily for 28 days (D28). Additionally, biochemical parameters, thiobarbituric acid reactive species (TBARS) levels in the liver, and histopathological analyses of the kidneys and liver were performed. Results: On the seventh day of treatment, a 74.7% reduction in glucose levels were observed in the group of diabetic animals treated with Mm (50 mg/kg bw) when compared to the beginning of the treatment. At D28, the hypoglycemic effect was maintained. The results of the biochemical and histopathological parameters and the TBARS levels suggest that this dry extract exerts nephro- and hepatoprotective effects. Conclusions: The findings demonstrate the potential that this extract has to inhibit the α-glucosidase enzyme, and it acts similarly to the positive control acarbose. Furthermore, this extract is nephro- and hepatoprotective. Therefore, this dry extract has the potential to be an adjuvant for DM2, which corroborates its use in folk medicine. Graphical abstract: Image 1 Highlights: Myrcia multiflora is used in Brazilian folk medicine to control diabetes. M. multiflora leaf extract showed a hypoglycemic effect in diabetes-induced mice. M. multiflora leaf extract inhibited lipid peroxidation in liver of diabetic mice. The dry extract of M. multiflora exerts nephron- and hepatoprotective effects.